2015
DOI: 10.1016/j.fitote.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chelidonium majus extracts and major alkaloids on hERG potassium channels and on dog cardiac action potential — A safety approach

Abstract: Chelidonium majus or greater celandine is spread throughout the world, and it is a very common and frequent component of modern phytotherapy. Although C. majus contains alkaloids with remarkable physiological effect, moreover, safety pharmacology properties of this plant are not widely clarified, medications prepared from this plant are often used internally. In our study the inhibitory effects of C. majus herb extracts and alkaloids on hERG potassium current as well as on cardiac action potential were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…The berberine of the I to blockade is different from the disopyramide and quinidine because it is not accompanied by an inward sodium current inhibition [12]. Another research has shown that it may lead to the prolongation of the QT interval and increase the risk of ventricular arrhythmias [13]. Furthermore, we used voltage clamp operations to observe that berberine had significant inhibitory effects that delayed the potassium current, and not the sodium current, which is the extension of the myocardial cells and one of the important mechanisms underlying antiarrhythmia.…”
Section: Alkaloidsmentioning
confidence: 99%
“…The berberine of the I to blockade is different from the disopyramide and quinidine because it is not accompanied by an inward sodium current inhibition [12]. Another research has shown that it may lead to the prolongation of the QT interval and increase the risk of ventricular arrhythmias [13]. Furthermore, we used voltage clamp operations to observe that berberine had significant inhibitory effects that delayed the potassium current, and not the sodium current, which is the extension of the myocardial cells and one of the important mechanisms underlying antiarrhythmia.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Moreover, its fresh latex has been also applied for the treatment of dermatological disorders, including warts and corns, tinea infections, and eczema (HMPC, ). C. majus purified compounds have been associated to a broad spectrum of biological effects, such as anti‐inflammatory, choleretic, antimicrobial, antiviral, analgesic, antispasmodic, and hepatoprotective; moreover, some studies have recently suggested anticancer properties (Orvos et al, ).…”
Section: Main Information Reported In the Websites Selling/describingmentioning
confidence: 99%
“…purified compounds have been associated to a broad spectrum of biological effects, such as anti-inflammatory, choleretic, antimicrobial, antiviral, analgesic, antispasmodic, and hepatoprotective; moreover, some studies have recently suggested anticancer properties (Orvos et al, 2015).…”
mentioning
confidence: 99%
“…[Ranunculaceae]), which possesses a variety of activities including anti-tumour, anti-inflammation, anti-atherosclerosis, and treating infectious diarrhea (Orvos et al 2015;Park et al 2015). Recent studies show that BBR could be used for the controlling arrhythmia, lowering blood lipid, lowering blood pressure and reducing blood sugar in clinical.…”
Section: Introductionmentioning
confidence: 99%